Advancing the study of life and death education: theoretical framework and research inquiries for further development - Phan, Huy P.; Chen, Si-Chi; Ngu, Bing H.; Hsu, Chao-Sheng (Frontiers in Psychology, 2023)
Life and death education, also known as life education and death education, is an interesting subject that may coincide with the subject of lifespan development. In brief, from our theoretical perspective, which guides our teaching and curriculum development, life education considers personal understanding of life functioning on a daily basis, whereas death education explores matters that are related to death and dying. For example, how can a social worker utilize his life knowledge, or life wisdom, to assist a relative to understand the intricate nature of death? In a similar vein, how can a senior citizen use her personal experience of Buddhist meditation practice to overcome a minor Covid setback? Central to our teaching practice is the premise of ‘active transformation’ (i.e., transforming life knowledge into positive practice) and the premise of ‘theoretical infusion’ (e.g., the infusion of a distinctive epistemological belief in the teaching of life) that would, in turn, help to enhance and facilitate deep, meaningful understanding of life and death. The purpose of the present article is for us to discuss a proposition of a theoretical-conceptual model, which depicts the ‘unification’ or integration of three major viewpoints of life and death: the social viewpoint, the philosophical viewpoint, and the psychological viewpoint. We theorize that unification of the three theoretical viewpoints may help provide grounding for effective teaching and holistic understanding of the subject contents of life and death. Such discourse, importantly, may also assist to advance the scope and complexity of the lifespan development subject. Finally, in addition to our theoretical-conceptual model of life and death, we propose three major research inquiries for development: the meaning of situated mindset, the underlying nature of spiritual transcendence, and proposition of appropriate methodological accounts for usage. Overall, then, we purport that our conceptual analysis and discussion overview, based on philosophical reflection, may serve to stimulate interest, intellectual curiosity, scholarly dialog, etc.